The policy of silence of the Brazilian agrarian problem: A política de silêncio do problema agrário brasileiro - Lerrer, Débora; de Almeida Forigo, Adriano (Programa de Pós-graduação em Desenvolvimento, Agricultura e Sociedade da Universidade Federal Rural do Rio de Janeiro (CPDA/UFRRJ), 2019)
The article “The policy of silence of the Brazilian agrarian problem” undertakes a reflection on the marginalization of the agrarian reform theme over recent years, based on the pathways revealed by a truncated local recollection obtained through fieldwork carried out in 2015 and 2016, about a land conflict of the 1950s in Paraná. The hypothesis of the article is that the silencing of the Brazilian agrarian problem and the consequent marginalization and political fragility of peasant-oriented public policies are products of the “divided memory” associated with the way in which the expansion of capitalism in the countryside is produced and reproduced. The progress brought by the “businessmen” is exalted and, at the same time, ambivalence is expressed regarding the violence that has established these enterprises in these regions.Keywords: struggle for land; silencing; public policy.LERRER, Débora; FORIGO, Adriano de Almeida. A política de silêncio do problema agrário brasileiro. Estudos Sociedade e Agricultura, v. 27, n. 3, p. 483-508, out. 2019.Submitted in July 2019.Accepted in August 2019.